2017
DOI: 10.14483/calj.v19n1.10219
|View full text |Cite
|
Sign up to set email alerts
|

eTandem Language Learning and Foreign Language Anxiety among Colombian learners of German

Abstract: Although eTandems, offering the opportunity of real life contact to speakers of one's target language, are suggested as an anxiety-reducing, confidence-increasing approach to language learning, these effects have not been investigated empirically. The aim of this article is to explore the experiences and perceptions of 11 Colombian learners of German as a foreign language who participated in a German-Spanish eTandem project. Data were collected by means of interviews and focus groups, and evaluated using quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
(33 reference statements)
2
1
0
Order By: Relevance
“…At the same time, students who are concerned over their pronunciation might greatly benefit from targeted training in pronunciation skills, as well as from online conversational practices, both in class and in conversing with native Maja Novak Lađarević: Examining the key factors behind foreign language anxiety (FLA) in online teaching of English for Specific Purposes (ESP) speakers. Such demand is in line with previous findings, which have already established the benefits of telecollaborative language practices (e.g Appel & Garcia, 2020;El-Hariri, 2017;Melchor-Couto, 2016). Interestingly, Martin et al (2022) demonstrated that anxious language learners highly welcome video feedback in online pronunciation tasks, which is certainly something to be considered, especially in the context of online language learning.…”
Section: The Main Predictors Of Fla In An Online Esp Classroomsupporting
confidence: 88%
See 1 more Smart Citation
“…At the same time, students who are concerned over their pronunciation might greatly benefit from targeted training in pronunciation skills, as well as from online conversational practices, both in class and in conversing with native Maja Novak Lađarević: Examining the key factors behind foreign language anxiety (FLA) in online teaching of English for Specific Purposes (ESP) speakers. Such demand is in line with previous findings, which have already established the benefits of telecollaborative language practices (e.g Appel & Garcia, 2020;El-Hariri, 2017;Melchor-Couto, 2016). Interestingly, Martin et al (2022) demonstrated that anxious language learners highly welcome video feedback in online pronunciation tasks, which is certainly something to be considered, especially in the context of online language learning.…”
Section: The Main Predictors Of Fla In An Online Esp Classroomsupporting
confidence: 88%
“…For example, Appel & Garcia (2020) demonstrated that FLA can be reduced over time by using e-tandem, a telecollaborative language learning practice commonly involving native speakers of different languages who converse in an online setting in order to learn each other's languages. Similar results were obtained by El-Hariri (2017), who confirmed that e-tandem has the potential of reducing anxiety and raising confidence among language learners, though such effects are not necessarily transferrable to foreign language classroom. Similarly, Melchor-Couto (2016) demonstrated that oral interactions with native speakers in virtual worlds can help in decreasing FLA in comparison to oral interactions in traditional classrooms.…”
Section: Introductionsupporting
confidence: 82%
“…Under the guidance of Vetter, the L3-TaSK project and FAME (Fostering Autonomy and Motivation), examine different aspects of eTandems as a means of linguistic cooperation across long distances. Whereas FAME focuses particularly on learners’ autonomy and motivation, including FL anxiety phenomena (see El-Hariri & Jung, 2015; El-Hariri, 2017), L3-TaSK provides insights into areas such as the learners’ L3 use, their beliefs and attitudes regarding telecollaborative task design, the teacher's role, task design for online collaborative interaction or conversational analysis perspectives of eTandem dialogues (El-Hariri, 2016; Fink, 2016; Kronsteiner & Vetter, 2016; Renner, Fink, & Volgger, 2016; Vetter, 2017). While learners of Chinese, Spanish and German have been involved in the L3-TaSK project, learners of French, Spanish and German in Austria, France and Colombia comprise the population of the FAME project.…”
Section: Findings: Research On Language Teaching and Learning In Austriamentioning
confidence: 99%